2019
DOI: 10.1002/ece3.5605
|View full text |Cite
|
Sign up to set email alerts
|

Development of high‐resolution DNA barcodes for Dioscorea species discrimination and phylogenetic analysis

Abstract: The genus Dioscorea is widely distributed in tropical and subtropical regions, and is economically important in terms of food supply and pharmaceutical applications. However, DNA barcodes are relatively unsuccessful in discriminating between Dioscorea species, with the highest discrimination rate (23.26%) derived from matK sequences. In this study, we compared genic and intergenic regions of three Dioscorea chloroplast genomes and found that the density of SNPs and indels in intergenic sites was about twice an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…In addition, no gene arrangements were detected either within D. alata or in comparison to its closely related species (i.e., D. brevipetiolata , D. cirrhosa , D. glabra , D. japonica, and D. polystachya ) ( Figure 2 ). These findings were also largely consistent with the characteristics of previously published plastomes of Dioscorea , which showed that the plastomes in this genus were well-conserved [ 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, no gene arrangements were detected either within D. alata or in comparison to its closely related species (i.e., D. brevipetiolata , D. cirrhosa , D. glabra , D. japonica, and D. polystachya ) ( Figure 2 ). These findings were also largely consistent with the characteristics of previously published plastomes of Dioscorea , which showed that the plastomes in this genus were well-conserved [ 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 91%
“…The same trend was observed on SPE as the highest values were on D. rotundata × D. burkilliana cross-combinations. This relatively higher cross-compatibility rate could be attributed to high genetic relatedness among these species, as reported by previous studies 22 , 25 , 29 – 31 . However, interspecific crosses involving D. rotundata with D. cayenensis had generally low success rates due to expected differences in ploidy level.…”
Section: Discussionsupporting
confidence: 76%
“…Three plastid loci usually showing high polymorphism and commonly used for DNA barcoding (e.g., Hollingsworth et al, 2011;Xia et al, 2019) were tested for amplification and sequencing. The plastid marker rps16 (with rpsF and rpsR2; Oxelman et al, 1997) did not amplify.…”
Section: Plastid Dna Sequencingmentioning
confidence: 99%